THE PORTRAIT OF BOYAR MOŢOC IN THE WORK OF COMPOSER GHEORGHE MUSTEA - GUŢANU STOIAN, Luminiţa (Studia Universitatis Babes-Bolyai Musica, 2017)
The present survey aims at emphasizing Gheorghe Mustea’s ability to create a musical portrait of Boyar Moţoc, in his opera, “Alexandru Lăpuşneanu”. The overall portrait the author creates for this historical figure includes his psychological profile, suggestively presented in three different states, outlined on the relationship between two pillars (cause and effect and premise - consequence).